2006
DOI: 10.1016/j.yexmp.2006.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the interleukin-4 and IL-4 receptor genes modify risk for chronic inflammatory arthropathies in women

Abstract: Polymorphisms in the interleukin-4 and IL-4 receptor genes modify risk for chronic inflammatory arthropathies in women. Suppiah, V., Rooney, M., & Vandenbroeck, K. (2006). Polymorphisms in the interleukin-4 and IL-4 receptor genes modify risk for chronic inflammatory arthropathies in women. AbstractRheumatoid and juvenile idiopathic arthritis (RA, JIA) are chronic inflammatory arthropathies with polygenic autoimmune background. We analysed the IL-4 +33 C/T and IL-4R Q551R single nucleotide polymorphisms (SNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…Interestingly, an IL-1α signature was found in the remaining ILAR subtypes, suggesting a mechanistic answer to differences in the efficacy of IL-1 blockade (IL-1 receptor antagonism versus specific anti–IL-1β therapy) in some children with nonsystemic arthritis (48,49). The key role of IL-4 in defining patient groups by sensitivity analysis supports earlier studies implicating Th2-related cytokines in moderating the pathogenesis of childhood arthritis (50,51). Using data alone, our analytical framework recovered important known biomarkers in JIA and provided a means to integrate these known biologic signals with important clinical signals to identify homogeneous patient subpopulations.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, an IL-1α signature was found in the remaining ILAR subtypes, suggesting a mechanistic answer to differences in the efficacy of IL-1 blockade (IL-1 receptor antagonism versus specific anti–IL-1β therapy) in some children with nonsystemic arthritis (48,49). The key role of IL-4 in defining patient groups by sensitivity analysis supports earlier studies implicating Th2-related cytokines in moderating the pathogenesis of childhood arthritis (50,51). Using data alone, our analytical framework recovered important known biomarkers in JIA and provided a means to integrate these known biologic signals with important clinical signals to identify homogeneous patient subpopulations.…”
Section: Discussionsupporting
confidence: 82%
“…Genetic differences between men and women have been implicated in distinct gender-specific patterns of susceptibility to many diseases, including autoimmune disorders [27,28]. Furthermore, some studies revealed female-specific associations between polymorphisms within genes related to the immune system and RA, suggesting the existence of genetic predisposition factors specific for women [29][30][31][32][33][34][35]. In the context of these reports, the present study focused on the female patient population with RA.…”
Section: Introductionmentioning
confidence: 99%
“…Our data indicate that the IL‐4 haplotypes tagged by the −589T allele reduce the risk of premature MI. Because atherosclerosis is classically considered to be a Th1‐mediated disease, the observed protective effect of the −589T allele would be in accordance with the delayed progression of other Th1‐type diseases such as rheumatoid arthritis and multiple sclerosis in carriers of the −589T allele or 33T allele [12–14,17]. Interestingly, the same haplotypes seem to enhance the severity of the disease in Th2‐type diseases such as severe asthma and IgA nephropathy [4,7], and were recently found to enhance the risk of stroke in a nested case–control study (OR 1.40; 95% CI 1.13–1.73) [22].…”
Section: Discussionmentioning
confidence: 97%
“…The role of IL‐4 in the development and progression of complex diseases has been studied using single nucleotide polymorphisms (SNPs) in the IL‐4 gene ( IL‐4 ) which are associated with IL‐4 expression. The rare alleles of these polymorphisms were found to be associated with high IL‐4 expression [3], elevated total serum IgE [4–6], increased severity and progression of asthma [3,7], IgA nephropathy [8], certain carcinomas [9,10], late onset disease in AIDS (however, not in all studies) [11–13] and Th1‐type diseases, such as multiple sclerosis [14,15] and rheumatoid arthritis [16,17].…”
Section: Introductionmentioning
confidence: 99%